VIDEO BEKAL MAKAN TRANDING, UPAYA MENGURANGI ANGKA STUNTING - Apriliani, Silvi; Sianturi, Risbon; Mulyana, Edi Hendri; Qonita, Qonita (Journal of Childhood Education, Development and Parenting, 2024)
Abstract Stunting is a condition where children lack proper nutrition and nutritional intake. Lack of understanding from various parties causes high levels of stunting, even from the smallest scope, namely parents who do not provide quality nutrition which is considered very fatal. Video creations for school lunches which have been trending recently are an answer to overcome this problem. This qualitative study aims to find out how effective the trending school lunch video is in having a good impact on the understanding of parents and teachers in providing quality and interesting food supplies, of course. This research compares two schools, which implement the provision of bergzi school meals, with schools that do not implement this process due to a lack of information or digital literacy regarding circulating videos. The collected data was analyzed using the "T Test" where the analysis process was carried out by looking at the differences between the two groups. The results of this research show that the trending school lunch videos have an impact on parents in serving similar food supplies based on nutritional fulfillment and creativity in serving food which can attract children's attention. This effort will run well if there is active collaboration between teachers and parents at school in implementing nutritious food supplies to reduce stunting rates. Keyword: School lunchcreation video, reduction efforts, stunting ABSTRAK Stunting merupakan kondisi dimana, anak kurang akan asupan gizi dan nutrisi dengan baik. Kurangnya pemahaman dari berbagai pihak menyebabkan tingginya angka stunting, bahkan dari lingkup terkecil yakni orang tua tidak mampu memberikan asupan yang berkualitas dan dianggap sangat fatal. Video kreasi bekal sekolah yang belakangan ini tranding menjadi suatu jawaban untuk mengatasi hal tersebut. Studi kualitatif ini memiliki tujuan untuk mengetahui efektivitas video bekal makanan sekolah yang tranding, yang memberikan dampak yang baik terhadap pemahaman orang tua dan guru dalam memberikan bekal makan yang berkuaitas dan menarik tentunya. Penelitian ini membandingkan dua sekolah, dimana yang menerapkan pemberian bekal makan sekolah bergzi, dengan sekolah yang tidak menerapkan proses tersebut dikarenakan, kurangnya informasi atau literasi digital akan video yang beredar. Data yang terkumpul dianalisis dengan “Uji T” dimana proses analisis dilaksanakan dengan melihat perbedaan anatara dua kelompok. Hasil penelitian ini menunjukan bahwa video bekal makan sekolah yang tranding memberikan dampak kepada orang tua dalam menyajikan bekal makanan yang didasarkan pada pemenuhan gizi dan kreatifitas dalam menyajikan makanan dimana hal tersebut dapat menarik perhatian anak. Upaya tersebut akan berjalan dengan baik apabila adanya kolaborasi aktif anatar guru dan orang tua di sekolah dalam menerapkan bekal makanan bergizi dalam mengurangi angka stunting. Kata Kunci: Video kreasi bekal sekolah, upaya mengurangi, stunting.